Business Strategy of Chemical Company Using SWOT and Business Model Canvas Approach - Haq, Ahmad Irwiyan; Singgih, Moses Laksono (Institut Teknologi Sepuluh Nopember, 2019)
Chemical business in water treatment has a potential growth in the future. Currently, PT A is a chemical company who leads market share in Indonesia compared to other competitors. Within next ten years, PT A should keep this level of competitiveness and improve the level of market share. Therefore, indispensable to analyze the business strategy in order to be ready to face upcoming competitiveness and opportunities. Analysis of strategy is conducted by SWOT approach. From this SWOT analysis, Internal Factor Evaluation (IFE) and External Factor Evaluation (EFE) matrix then took place to review this SWOT result. Furthermore, Business Model Canvas method is used to discuss more detail in every single block. During using Business Model Canvas, company representative is invited in Focus Group Discussion. Business Model Canvas is selected in this research due to it has comprehensive analysis about the nine variable that company running the business. From this research, it is known that company place at quadrant I of SWOTÂ diagram. IFE and EFE score is 3.54 and 2.40, respectively. This score plots at zone IV, which means Grow and Build, in IFE-EFE matrix. These result then become an input for BMC mapping. Improvement of BMC then recommended for key resources, key partnership, key activities dan channels. Strategy generated from this research then will be a recommendation to the management. Besides, this research also become a motivation for the researcher because so far there is no particular strategy development for water treatment business in power plant based on academic point of view